This time is the same: like the housing bubble, the Fed is ignoring the shale bubble in plain sight - Stockman, David (REVISTA PROCESOS DE MERCADO, 2015)
We are now far advanced into the third central bank generated bub-ble of the last two decades, but our monetary politburo has taken no notice whatsoever of its self-evident leading wave. Namely, the massive malinvestments and debt mania in the shale patch. Call them monetary bourbons. It is no exaggeration to say that inhabitants of the Eccles Building deserve every single word of Talleyrand’s famous epithet: «They learned nothing and forgot nothing». To wit, during the last cycle they claimed to be fostering the Great Moderation and permanent full employment prosperity. It didn’t work. When the housing and credit bubble blew-up, it washed out all the phony gains from the Greenspan/Bernanke printing spree. By the time the liquidation was finished in early 2010, there were 2 million fewer payroll jobs than there had been at the turn of the century. Never mind. The Fed simply doubled-down. Instead of expand-ing its balance sheet by 50%, as happened during the eight years between 2000 and 2008, it went into monetary warp drive, balloon-ing its made-from-thin-air liabilities by 5X in only six years.